Amiri Baraka: The Significance of Allusions (References) In The Slave - Suwyid, Safyah Saad (Eximia, 2022)
The play The Slave by Amiri Baraka has caused major disturbance since 1964. Baraka’s writing seems to get on the nerves of the white people because it boldly presents the real inner and outer struggle of black men with a white system. This paper will analyzes Amiri Baraka’s play The Slave. The main purpose of this paper is to pin point the significance of allusions/references in Baraka’s play. The allusions that have been discussed are three: the reference to Yeats’s poem “News For The Delphic Oracle” and the reference of bad poetry to carl Sandburg. The last reference is to Bigger Thomas the leading character in the novel Native Son.